2012
DOI: 10.5551/jat.13037
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Visceral Fat and Multiple Risk Factor Accumulations is Strongly Associated with Coronary Artery Disease in Japanese (The VACATION-J Study)

Abstract: Aim: Multiple risk factor syndrome is a target for the prevention of coronary artery disease (CAD).A cluster of multiple risk factors, such as hypertension, glucose intolerance, and/or dyslipidemia, is encountered in Japanese without and with excess visceral fat. The present study investigated the relationship between multiple risk factor accumulation and CAD in Japanese without and with visceral fat accumulation. Methods: The study subjects comprised 257 Japanese with suspected CAD (males/females= 153/ 104), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 22 publications
1
20
0
2
Order By: Relevance
“…Lear et al claimed that VAT is the primary adiposity associated with atherosclerosis and likely represents an additional risk factor for carotid atherosclerosis in men (26). Shimizu et al contended that VAT accumulation acts in concert with CRF accumulation to increase the risk for CAD (27). Our results showed that men had a higher VAT volume and a significant association with extensive extraaortic arterial 18 F-FDG accumulation and suggest that VAT both played a key role in the extensive extraaortic arterial 18 F-FDG accumulation in the men examined and was related to the development of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Lear et al claimed that VAT is the primary adiposity associated with atherosclerosis and likely represents an additional risk factor for carotid atherosclerosis in men (26). Shimizu et al contended that VAT accumulation acts in concert with CRF accumulation to increase the risk for CAD (27). Our results showed that men had a higher VAT volume and a significant association with extensive extraaortic arterial 18 F-FDG accumulation and suggest that VAT both played a key role in the extensive extraaortic arterial 18 F-FDG accumulation in the men examined and was related to the development of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Although the VFA at the umbilicus has been widely used to identify visceral obesity13, 14, 15, 16, 17, 18, 19, we previously showed that the maximal VFA was not at the umbilicus, but was widely distributed from L1 to L520, 21.…”
Section: Introductionmentioning
confidence: 93%
“…In contrast, the Japan Society for the Study of Obesity (JASSO) has recommended that the appropriate cut‐off values of WC for detecting visceral obesity are 85 cm in Japanese men and 90 cm in Japanese women from the general population12, and these values are widely used for diagnosis of MetS in Japan. As the JASSO cut‐off value of WC is higher for women than men, unlike the criteria used in other Asian countries, reassessment of the cut‐off values for Japanese persons has been carried out previously, and different values have been proposed13, 14, 15, 16, 17, 18, 19. However, these previous Japanese studies were based on WC and/or the visceral fat area (VFA) at the umbilicus determined by CT scanning.…”
Section: Introductionmentioning
confidence: 99%
“…A Japanese study, the VACATION-J study, found a similar result. The coexistence of visceral fat (visceral adipose tissue volume ≥ 100 cm 2 ) and risk factor accumulations (i.e., hypertension, glucose intolerance, and/or dyslipidemia) is strongly associated with coronary artery disease in the Japanese population [22]. Moreover, the study in Shanghai by Zhang et al [23] revealed that the CVD incidence was independently related to increased waist circumference in the middle-aged group and to elevated blood glucose in the elderly group.…”
Section: The Epidemiology Of Obesity and Associated Changes Over The mentioning
confidence: 97%